PENGARUH MOTIVASI, DUKUNGAN ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. ASEAN MOTOR INTERNASIONAL (DFSK) KOTA BENGKULU - Fahrezi, Angga; Bahrun, Khairul (UM. Bengkulu, 2025)
This research aims to determine the influence of motivation, organizational support and work discipline on employee performance at PT. Asean Motor International (DFSK) Bengkulu City. This type of research is a quantitative descriptive type of research, the object of this research is the employees of PT. Asean Motor International (DFSK) Bengkulu City. The sampling method uses a non-probability technique, namely accidental sampling. The number of respondents in this study was 40 people. The data collection method uses a questionnaire. The data analysis technique uses the Multiple Linear Regression Analysis Test, and Hypothesis Testing, namely the t test and f test. The results of this research can be concluded that the Motivation variable has a positive effect on Employee Performance, Organizational Support has a positive effect on Employee Performance, Work Discipline has a positive effect on Employee Performance, and Motivation, Organizational Support and Work Discipline together have a positive and significant effect on Employee Performance.Keywords: Motivation, Organizational Support, Work Discipline, Employee Performance.